A Reading of Westcott's Gospel of Creation: An Early Venture into Ecological Theology?. Issue 2 (2nd August 2013) - Reid, Duncan
Abstract In response to the contemporary ecological movement, ecological perspectives have become a significant theme in the theology of creation. This paper asks whether antecedents to this growing significance might predate the concerns of our times and be discernible within the diverse interests of nineteenth-century Anglican thinking. The means used here to examine this possibility is a close reading of B. F. Westcott's 'Gospel of Creation'. This will be contextualized in two directions: first with reference to the understanding of the natural world in nineteenth-century English popular thought, and secondly with reference to the approach taken to the doctrine of creation by three late twentieth-century Anglican writers, two concerned with the relationship between science and theology in general, and a third concerned more specifically with ecology.